SEKULARISME POLITIK PERSPEKTIF ABDULLAHI AHMED AN-NA‘IM - Zulkifli Zulkifli (Kalam: Jurnal Agama dan Sosial Humaniora, 2017)
This articles explores the thought of Abdullahi Ahmed an-Na'im's about the relation of Islam and the state, focusing on the concept of secularism. This theme has become an interesting discourse studied by academics including an-Na'im. However, in addressing the issue of secularism, an-Na'im has different methods and approaches with previous Islamic thinkers both from the traditionalists even from secular circles though. For an-na'im, secularism is an important concept as a mediation space between religion and state.